An Updated Bibliometric Analysis on Sars-Cov-2 (Revista Científica Ciencias Naturales y Ambientales, 2021)
In Wuhan, the first and only cases of a new coronavirus were detected, called SARS-CoV-2, which is a respiratory disease that presents mild symptoms in its infected and in other types of patients it can develop deadly situations. The main objective of this study was to analyze how the scientific production of covid-19 has evolved through a bibliometric study. Within the implementation of materials and methods, a bibliographic search was carried out through three highly prestigious databases such as Web of science, Scopus and PubMed, where several structural strata related to the country of origin, the most productive authors and keywords were identified. Taking into consideration that the results showed the analysis of 98,458 scientific articles from quartile 1 - 2 which identified the Chinese Academy of Science as the organization that is part of the elite in covid-19 research, however it was identified that the base of data that contributed the most in this research was Web Of Science with a total of 46,418 articles refereed in the year 2021 and that the most searched keyword worldwide was covid-19. Finally, the study evidenced the participation of each of the higher education units, first world countries and experts on SARS-CoV-2 working together to obtain the highest number of answers about this virus that paralyzed the world.
Keywords: Bibliometrics; Coronavirus; Covid-19; Sars-cov-2; 2019-ncov2